2020
DOI: 10.28926/briliant.v5i3.490
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Kemampuan Pemecahan Masalah Siswa Materi Fluida Statis

Abstract: Salah satu komponen kunci dalam pembelajaran fisika adalah siswa memiliki kemampuan dalam memecahkan masalah. Penelitian ini bertujuan untuk mengidentifikasi kemampuan pemecahan masalah siswa pada materi fluida statis. Metode deskriptif dengan pendekatan kualitatif diterapkan pada 43 orang siswa kelas XII IPA. Instrumen yang digunakan berupa 3 butir soal uraian materi fluida statis. Hasil penelitian menunjukkan rata-rata kemampuan pemecahan masalah siswa sebesar 59,60 (kategori sedang). Persentase siswa yang t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The research results showed that the average student's problem-solving ability was 59.60 (medium category). The percentage of students who fall into the novice category is 86.0% (hydrostatic pressure), 88.4% (Pascal's law), and 55.8% (Archimedes' law) (Estianinur, 2020). Students still experience difficulties in applying strategies so they cannot solve problems well.…”
Section: Introductionmentioning
confidence: 99%
“…The research results showed that the average student's problem-solving ability was 59.60 (medium category). The percentage of students who fall into the novice category is 86.0% (hydrostatic pressure), 88.4% (Pascal's law), and 55.8% (Archimedes' law) (Estianinur, 2020). Students still experience difficulties in applying strategies so they cannot solve problems well.…”
Section: Introductionmentioning
confidence: 99%